Examining the Impact of the Bubat War Event from the Perspective of Subjectivism in the Modern Era - Pangestu, Ghalih Purwo; Abrar, Abrar; Nurzengky, Nurzengky; Marta, Nuraeni; Kurniawati, Kurniawati (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to understand the dynamics of changes in Sundanese identity after the Bubat War, and how this event continues to influence their views on history and culture into the contemporary era. The research method used in this study is a qualitative method with a historical approach. The purpose of this method is to understand the historical context in a structured manner and its impact on certain events or phenomena. The results of this study indicate that the Bubat War had a significant impact on the identity and culture of the Sundanese and Javanese people. This history not only left disappointment, but also created perspectives and cultural attitudes that were passed down from generation to generation. However, the positive impact of this event strengthened the identity of each tribe as an independent and competitive group. In addition, it can be said that in this modern era, the negative impact of the Bubat War itself has begun to erode and fade.